Endocrinopathies in thalassemia - a review (IMC Journal of Medical Science, 2021)
Improved treatment has increased survival of patients with thalassemia. However, they still suffer from several endocrine complications mainly as a result of iron overload from multiple transfusions. Endocrinopathies manifest as early as the first decade of life, affecting growth, puberty, psychological development and quality of life. The presence of concomitant anemia, chronic liver disease and cardiomyopathy affect the development and treatment of endocrine disorders, making endocrinopathies in thalassemia a complex disorder. This review focuses on the pathogenesis, diagnosis and treatment of endocrinopathies in transfusion and non transfusion dependent thalassemia. The main points that should be considered in the management of endocrine disorders in a patient with thalassemia are highlighted in this review.Ibrahim Med. Coll. J. 2021; 15(1): 47-55